Sulfuros másicos obtenidos a partir de óxidos mixtos de alta área específica como catalizadores de hidrotratamiento (2010)
ABSTRACT: Several bimetallic Ni-Mo, Co-Mo and Co-W materials were prepared by co-precipitation and a Ni-W material through hydrothermal synthesis. The characterization by X-ray diffraction (XRD) of molybdates confirmed the formation of layered fy phase, while the tungstates showed both fy semicrystalline and wolframite. The thermal analyses (TGA and DTA) of these materials showed phase transition around 400°C, excepting by CoMofy to 350°C; these temperatures were selected to calcine the bimetallic precursors to obtain mixed oxides, which exhibited high specific surface areas as compared to analogous materials reported by different synthesis pathways. The Fourier transformed infrared spectroscopy (FTIR) confirmed the phase formation of the species in precursors and mixed oxides. The catalytic activity of the sulfurated mixed oxides was simultaneously evaluated in the hydrodesulphurization (HDS) of dibenzotiophene (DBT) and the hydrogenation (HYD) of tetraline. Results showed a similar behavior to commercial catalysts. The effect of promotors (Ni and Co) is discussed.